Partes de guerra antes de la guerra - Ángel Bahamonde Magro (Mélanges de la Casa de Velázquez)
This paper examines the situation reports issued by the different organic divisions of the General Staff and the Ministry of War during the spring of 1936 and the post-war sanction procedures against active, reservist or retired professional soldiers who remained in the republican zone, offering a kaleidoscopic view of the «national» military mentality and the reasons for the insurgency. This body of officers devised a dichotomic discourse on the situation, where the «revolution» in preparation since the triumph of the PF was combated by an Army which, as the ultimate guarantor of the social order, was presented as the sole antidote to that revolution. The old discourse of a neutral, mediatory Army that would restore social harmony to the benefit of the country as a whole was already in question in 1931 and thereafter gave way to a belligerent discourse founded on active maintenance of the social order against the revolution, which may reasonably be described as «fascistic».